Case Report: Rapid Recognition and Immune Modulation of Secondary HLH Due to Disseminated HSV Infection - McKeone, Daniel J.; DeMartini, Theodore K. M.; Kavanagh, Robert P.; Halstead, E. Scott (Frontiers in Pediatrics, 2021)
We describe the case of a newborn who presented with multiple organs dysfunction syndrome (MODS) and hyperferritinemia, who eventually met criteria for hemophagocytic lymphohistiocytosis (HLH) due to disseminated herpes simplex virus 1 (HSV-1). While the cytokine storm abated after administration of multiple immune modulatory therapies including dexamethasone, etoposide, intravenous immune globulin, anakinra, as well as the interferon gamma antagonist emapalumab, multiple organ dysfunction syndrome progressed. Care was withdrawn after five days. Subsequent genetic testing did not reveal any mutations associated with familial HLH. This case highlights that even with appropriate antiviral treatment and immune suppression, disseminated HSV is often fatal. Further study is warranted to determine whether early immune modulatory therapy including interferon gamma blockade can interrupt the HLH inflammatory cascade and prevent progression of MODS.